The synthesis of new polymeric sorbent and its application in preconcentration of cadmium and lead in water samples - Senkal, B. Filiz; Ince, Muharrem; Yavuz, Erdem; Yaman, Mehmet (Elsevier Science Bv, 2007)
Metal determinations at low concentration levels (<= ng mL(-1)) comprise one of most important targets in analytical chemistry. This interest also increases in different areas such as biology, medicine, environment and food samples. In spite of inherent high sensitivities obtained for electrothermal atomic absorption spectrometry (ETAAS) and inductively coupled plasma-mass spectrometry (ICP-MS), these techniques have some limitations depending on the concomitants. As a result, interest in preconcentration techniques still continues increasingly for trace metal determinations by flame atomic absorption spectrometry (FAAS) due to the high accuracy of this method. In this work, thioureasulfonamide resin was synthesized, characterized and applied as a new sorption material for determinations of cadmium and lead in water samples. The method is based on the sorption of Cd and Ph ions on the synthesized resin without using any complexing reagent. The optimization of experimental conditions was performed using factorial design including pH, amount of resin, contact time, first sample volume and final eluent volume. Using the experimental conditions defined in the optimization, the method was applied to the determination and preconcentration of Cd and Pb at ng mL(-1) level in natural water. Flame AAS was used for trace metal determinations. This method exhibits the superiority in compared to the other adsorption reagents because of the fact that there is no necessity of any complexing reagent and optimum pH of solution presents in acidic media. Consequently, 600- and 360-fold improvements in the sensitivity of FAAS were achieved by combining the slotted tube atom trap-atomic absorption spectrometry (STAT-FAAS) and the purposed enrichment method for Cd and Pb, respectively. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: thioureasulfonamide resin; preconcentration; cadmium; lead; water analysis